Salmonella infection accelerates postnatal maturation of the intestinal epithelium - Stefan Schlößer; Anna-Lena Ullrich; Nastaran Fazel Modares; Matthias A. Schmitz; Johannes Schöneich; Kaiyi Zhang; Isabel Richter; Laura Robrahn; Sarah Schraven; James S. Nagai; Sven-Bastiaan Haange; Susan A. V. Jennings; et al. (Proceedings of the National Academy of Sciences, 2025)
Postnatal establishment of enteric metabolic, host–microbial and immune homeostasis is the result of precisely timed and tightly regulated developmental and adaptive processes. Here, we show that infection with the invasive enteropathogen Salmonella Typhimurium results in accelerated maturation of the neonatal epithelium with premature appearance of antimicrobial, metabolic, developmental, and regenerative features of the adult tissue. Using conditional Myd88-deficient mice, we identify the critical contribution of immune cell-derived mediators. Cytokine stimulation of neonatal intestinal epithelial stem cell organoids suggests a network of synergistic and antagonistic cytokine effects with a significant contribution of IL-22, IL-4/IL-13, TNF, and IL-6 to infection-induced enterocyte reprogramming. Our findings demonstrate that the infection-associated immune cell activation disrupts physiological postnatal tissue maturation and may thereby worsen clinical outcomes and alter the neonatal-adult transition.